Micropropagation of Vanda Sp Orchids by Giving Various Concentrations of Potassium Nitrate (Kno3) and Thiamin to Murashige and Skoog Media In-Vitro - Anggara, Prapasta Puji; Seprido, Seprido; Nopsagiarti, Tri (Fakultas Pertanian Universitas Muara Bungo, 2023)
The Vanda sp orchid is an endemic flower that is widespread throughout Indonesia. Generative propagation of Vanda sp orchids takes a long time because the seeds are very small and do not have endosperm. Tissue culture techniques can be used to propagate Vanda sp orchids. The aim of the research was to determine the effect of giving potassium nitrate (KNO3) and Thiamin on Vanda sp orchid explants on Murashige and Skoog (MS) media in vitro. The design used was a Completely Randomized Factorial Design consisting of two factors, namely KNO3 (Without KNO3 /control, 1,700 mg/l, 1,900 mg/l, and 2,100 mg/l), the second treatment Thiamin (Without Thiamin /control, 0 .1 mg/l, 0.5 mg/l, and 0.9 mg/l. The research results showed that the concentration of Potassium Nitrate (KNO3) alone had a significant effect on all parameters, the best treatment was at a KNO3 concentration of 1,900 mg/l with an average 4.08 shoots and a height of 1.44 cm, 5.56 roots and a root length of 1.35 cm, while the highest number of leaves was 4.50, the best concentration of KNO3 was 2,100 mg/l. Thiamin treatment alone had a significant effect on The parameter for the number of leaves was 4.33 at a Thiamin concentration of 0.5 mg/l, for the number of roots was 5.06 at a Thiamin concentration of 0.9 mg/l. The interaction between KNO3 and Thiamin had a significant effect on the number of leaves, 5.11 at the KNO3 combination. 2,100 mg/ and Thiamin 0.5 mg/l, while the number of roots was 6.22 in the combination of KNO3 1,900 mg/ and Thiamin 0.1 mg/l.